Comparative performance evaluation of tele-operated pipe laying. - Junbok Lee
Excavation, in particular, trenching, presents a hazardous working environment for workers. Many deadly accidents still occur even though the Occupational Safety and Health Administration has increased its training for safe trenching. The work presented in this paper originated with the belief that the best approach to remedy this problem is technology. Its premise is the need to remove the workers from this deadly trap and replace them with mechanical device capable of doing the work necessary to lay pipes accurately. Presented is the results of a comparative field evaluation designed to prove that such a technology is not only technically feasible, but also cost-effective. For this purpose, a tele-operated pipe manipular was builds, capable of being easily attached to an excavator bucket and controllable from the safety of an operator cabin. The new technology was subsequently evaluated during field tests using both qualitative and quantitative performance criteria. Data from the study clearly demonstrate that this technological intervention not only works as intended, but also promises to reduce the cost of installing pipes, especially with increasing trench depths.
Keywords: Pipes; Trenching; Installation